Effects of Butyrate-Based Feed Additives on Nursery Pig Performance, Fecal Consistency, Blood Criteria, and Short Chain Fatty Acid Production - Ethan B. Stas; Ying Chen; Ross Wolfenden; Jamil E. G. Faccin; Jason C. Woodworth; Mike D. Tokach; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 300 pigs (241 × 600, DNA, initially 12.2 lb) were used to evaluate the effects of butyrate-based feed additives on nursery pig performance, fecal consistency, blood criteria, and short chain fatty acid (SCFA) concentration in the duodenum, jejunum, ileum, and cecum. At weaning, pigs were allotted to one of six dietary treatments based on initial body weight. There were five pigs per pen and 10 replications per treatment. Dietary treatments were arranged in a one-way treatment structure consisting of a negative control, a positive control, and four additional diets containing various butyrate- based feed additives. The negative control was a standard corn-soybean meal-based diet with no antibiotics or pharmacological levels of Zn or Cu. The positive control contained 3,000 and 2,000 ppm of Zn from ZnO in phase 1 and 2 respectively, and 250 ppm of Cu from CuSO4 in phase 3. The positive control also contained 55 ppm of carbadox (Mecadox; Phibro Animal Health Corp., Teaneck, NJ) across all three phases. The four butyrate-based feed additives were added at 0.1% to the negative control diet and consisted of encapsulated butyrate, monobutyrin, mono + tributyrin, and tributyrin (Eastman Chemical, Kingsport, TN). The mono + tributyrin additive contained 71.5% monobutyrin and 28.5% tributyrin. Pigs were fed phase 1 diets for 10 d (d 0 to 10), phase 2 diets for 14 days (d 10 to 24), and phase 3 diets for 14 d (d 24 to 38). Overall (d 0 to 38), pigs fed the positive control had increased (P < 0.05) ADG and ADFI compared to the other treatments. In addition, pigs fed mono + tributyrin had improved (P < 0.05) F/G compared to pigs fed monobutyrin with other treatments intermediate. There was a treatment × day interaction (P = 0.042) for fecal DM where on d 5, there were no differences in fecal DM between treatments (P > 0.10); however, on d 10, pigs fed the positive control had increased (P < 0.05) fecal DM compared to all other treatments. On d 38, pigs fed encapsulated butyrate had increased (P < 0.05) haptoglobin concentration compared to pigs fed the positive control with the other treatments intermediate. There was a treatment × day interaction observed (P < 0.001) for vitamin E where pigs fed tributyrin had higher (P < 0.05) vitamin E concentration on d 10 compared to pigs fed the negative control, the positive control, and monobutyrin with the other treatments intermediate, and no differences observed on d 38. Pigs fed mono + tributyrin had higher (P < 0.05) butyrate concentrations in the cecum compared to pigs fed the negative control with all other treatments intermediate. In summary, nursery pigs fed pharmacological levels of Zn and Cu along with carbadox improved growth performance as expected. Various butyrate-based feed additives had similar effects on nursery pig performance and SCFA in the small intestine. However, mono + tributyrin was associated with higher butyrate levels in cecum, potentially benefiting the epithelial cells.
Keywords: butyrate; short chain fatty acids; nursery pig; serum chemistry